The Ages and Stages Questionnaire: Social-Emotional—What Is the Optimal Cut-Off for 3-Year-Olds in the Swedish Setting? - Vaezghasemi, Masoud; Eurenius, Eva; Ivarsson, Anneli; Richter Sundberg, Linda; Silfverdal, Sven Arne; Lindkvist, Marie (Frontiers in Pediatrics, 2022)
ABSTRACT Objective: Expressions of emotional and behavioural symptoms in preschool age can predict mental health problems in adolescence and adulthood. The Ages and Stages Questionnaires: Social-Emotional (ASQ:SE) has been successful in detecting social and emotional problems in young children in some countries but had not been tested in Sweden. The objective of this study was to determine the optimal cut-off for the ASQ:SE instrument when administered to 3-year-old children in a northern Swedish setting, using the Strengths and Difficulties Questionnaire (SDQ) as the reference. Methods: The ASQ:SE (36-month interval, first edition) was administered at routine 3-year-olds’ visits to Child Health Care centres in Region Västerbotten, Sweden. During the study period (September 2017 to March 2018) parents were invited to also fill out the SDQ (2-4 year version). In the final analyses 191 children fulfilled the criteria for inclusion in the study sample. Non-parametric Receiver Operating Characteristic analysis was performed to quantify the discriminatory accuracy of ASQ:SE based on SDQ. Results: The Pearson correlation between ASQ:SE and SDQ indicated strong correlation between the two instruments. The Receiver Operating Characteristic curve showed good accuracy of ASQ:SE in relation to SDQ. However, our results suggest that the existing ASQ:SE cut-off score of 59 was not optimal in the Swedish context. Changing the cut-off from 59 to 50 would allow us to detect 100% (n=14) of children with problems according to SDQ, compared to 64% (n=9) when the cut-off was 59. However, the proportion of false positives would be higher (8% compared to 3%). Conclusion: The main finding was that for 3-year-olds in Sweden a decreased ASQ:SE cut-off score of 50 would be optimal. This would increase the detection rate of at-risk children according to SDQ (true positive), thus prioritising sensitivity. Our conclusion is that, although this change would also result in more false positives, this would be justifiable.